Mechanization for road and bridge construction a review of the interaction between design and specification and the use and development of mechanized methods : proceedings of a symposium by the Institution of Civil Engineers and the Institution of Highway Engineers held on 17 February, 1972 in London - Mayall, Kirstine S. L. (Institution of Civil Engineers, 1972)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a symposium held on 17 February 1972.